2017
DOI: 10.3390/ijgi6050134
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Distribution Patterns of High Performance Taxis from Big Trace Data

Abstract: Abstract:The unbalanced distribution of taxi passengers in space and time affects taxi driver performance. Existing research has studied taxi driver performance by analyzing taxi driver strategies when the taxi is occupied. However, searching for passengers when vacant is costly for drivers, and it limits operational efficiency and income. Few researchers have taken the costs during vacant status into consideration when evaluating taxi driver performance. In this paper, we quantify taxi driver performance usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…We divide the urban rail transit service area into grid cells and split the time axis into several time slots using a 2-h interval. We consider the service scope of the rail station [29] and the effect of granularity of grid cell on algorithm accuracy [30] when defining the scale of the spatial analysis unit. Since the time regularity of the travel demand hinges on the rhythm of residents' daily lives, the time interval in this study was determined by referring to previous research [28].…”
Section: ) Construction Of Travel Demand Matrixmentioning
confidence: 99%
“…We divide the urban rail transit service area into grid cells and split the time axis into several time slots using a 2-h interval. We consider the service scope of the rail station [29] and the effect of granularity of grid cell on algorithm accuracy [30] when defining the scale of the spatial analysis unit. Since the time regularity of the travel demand hinges on the rhythm of residents' daily lives, the time interval in this study was determined by referring to previous research [28].…”
Section: ) Construction Of Travel Demand Matrixmentioning
confidence: 99%
“…[11] fit an econometric model of driver income with five strategic factors that may explain income difference, and found that the significant factors are (in descending order of contribution) delivery speed, search distance, supply-demand ratio, and trip fare, while search intensity is not statistically significant. [12] found that taxis with high single-trip efficiency, defined as the average income rate between two consecutive pickups, usually avoid traffic and seek locations with high passenger demand. Among studies of this kind, [13] is perhaps the largest in scale to date.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al (2019) used the vehicle trajectory data to extract coach operation information such as coach stations, routes and timetables, which provided data support for China's national road passenger transportation ticketing platform. Some studies used taxi trajectory data to conduct passenger-finding strategies, spatiotemporal analysis of public transportation, road networks update and other studies to optimize urban traffic (Wu et al, 2016;Tang et al, 2017;Tu et al, 2018). Scholars also used mobile phone traces to study residents' mobility laws to assist scientific and smart city planning (Jiang et al, 2013;Chen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%